(untitled) (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2025)
The psychoeducation program “Building Self-Confidence and Achieving Success through Technology” was implemented to enhance the self-confidence and technological self-efficacy of vocational high school students at SMK Negeri 1 Jakarta. The program was motivated by the condition that some students showed a sufficient level of confidence in using digital technology, which affected their learning motivation and academic engagement. The objective was to strengthen students’ confidence and readiness for digital learning demands. The methods included a needs assessment through observation, interviews, and pre-test; implementation through interactive lectures, digital application simulations, educational games providing mastery experiences, and group reflection; and evaluation using a post-test analyzed with the Wilcoxon Signed-Rank Test. A total of 37 students from three study programs participated in the one-day activity. The results indicated a significant improvement in self-confidence scores from 34.11 to 35.57 (p < 0,001), accompanied by positive behavioral changes such as greater initiative in using technology and increased participation. These findings confirm that experiential learning–based psychoeducation is effective in fostering vocational students’ confidence in digital learning. The program is recommended for continuous implementation and replication in other schools.